Wetting and Adhesive Forces on Rough Surfaces – An Experimental and Theoretical Study. (2015) - Fritzsche, Jörg; Peuker, Urs A.
Abstract: It is well known that wetting plays a crucial role in many processes due to its impact on the emerging adhesive forces. In general, high wetting angles between solid and liquid lead to higher adhesive forces and vice versa. For ideal systems the calculation of these adhesive forces is possible using analytical approaches for van der Waals and polar forces. But there is still a lack of knowledge how to consider impacts like roughness and irregular shape of the solids during the calculation. The present paper aims to show the correlation between wetting behaviour and adhesive forces for non-ideal systems. Therefore, a model system is created wherewith the wetting angle can be changed in a high range. Coated alumina particles are used as solids in this model system. The coating leads to a low surface energy and consequently to a high wetting angle to water of 105°. The wetting angle is reduced by adding ethanol to the aqueous phase and thus the influence of wetting on the adhesive force can be investigated. To correlate the wetting angle with the adhesive force, both of them must be measured. Using a substrate with the same surface coating as the used particles the sessile drop method for the determination of the wetting angle can be applied. Subsequently, the calculation of the interfacial energy, which should be linked up directly to the adhesive force, is possible. The adhesive forces are determined directly by using an atomic force microscope (AFM). Therefore, a coated alumina particle is glued on the end of the cantilever to measure the particle-substrate force directly. The particle and substrate are entirely submerged into the surrounding liquid. As confirmed, measurements of the wetting angle show a decrease with higher ethanol fractions. This is due to the lower surface energy of ethanol compared to water. Furthermore, the results show a selective adsorption of ethanol to the solid surface. This leads to an increased surface saturation of ethanol depending on the concentration in the liquid which can be described with a Langmuir isotherm. AFM measurements show a variation of adhesive forces caused by the high roughness of the substrate. This can be described with statistical distributions. Parameters of this distributions show a correlation to the ethanol saturation. Semi-empirical approaches using van der Waals and polar forces confirm this behaviour.